UNSUR-UNSUR PARAGRAF NARASI DALAM BAHASA JAWA - Sri Nardiati (Humaniora, 2015)
Every human being involves in story activity. Therefore, the elements of NP (narrative paragraph) in Javanese should be investigated. The aim of investigation is to describe every element based on the character and the chronological event, its direct utterance, and the writer’s point of view. The scope of narrative paragraph study covers lingual unit of paragraph, sentence, clause, phrase, and word. The approach used is structural descriptive. The data is obtained by using listening and noting technique. The analysis uses orthografic method and distributional method, by using direct element division technique and then omission, substitution, insertion, and reversion. Narrative paragraph (NP) elements are participant and event. Participant element is filled with a character or more. Event element comprises of act, process, or state verb that relates to each other as stimulus-responsse. NP usually has direct utterance that is unmarked and marked. The mark is located in the beginning, middle, and the ending. NP is written based on the point of view, both the first and third person. In the first point of view, the character is central character or an observer, which is marked by using I (aku, saya) pronoun; meanwhile, in the third person point of view is marked by he/ she (ia/dia/dheweke) pronoun.